Muhammadiyah International Class Orientation Program: EPP Assessment Experience - Yusuf, Arba’iyah; Manggiasih, Laras Ayuningtyas; Padmasari, Arumtyas Puspitaning; Hidajati, Fitrijah (ICONELT, 2022)
Muhammadiyah develops International Class Orientation as the approach to improve the quality of Education. It is because Muhammadiyah as private organization has a challenge how to convince society that its education is really qualified. Since 2013, Muhammadiyah makes the memorandum of understanding with ACT Education Solution on EPP (English Proficiency Program). For the purpose of improving quality, 4 (four) Muhammadiyah Schools implement English Proficiency Program in East Java. This program has special way of assessment called assessment folder in which consists of writing program, interactive role play, unit tests, mid-program test, portfolio, individual oral presentation, group project, and end of program test. Muhammadiyah International Class Orientation has experiences regarding those types of assessment for several years. The research on Muhammadiyah International Class Orientation regarding EPP Assessment Experience was conducted since the other research hasn’t explored by others. The study is using qualitative research by identifying 4 schools as the places of the study. It gives insight to other teachers in assessing students’ learning in a various way.